Розрахунок просторового розподілу компонентів бінарної суміші в плоскій порі з несиметричним пристінковим потенціалом - Булавін, Л.А.; Гаврюшенко, Д.А.; Сисоєв, В.М.; Якунов, П.А. (Видавничий дім "Академперіодика" НАН України, 2008)
The liquid lattice model is examined to calculate the binary solution component concentration. The expansion of an external field potential in a functional Taylor series is constructed to obtain an expansion in direct correlation functions of all orders. The quantitative criteria for applications of the expression are indicated. The expansion of the binary solution concentration in a functional Taylor series is obtained to gain the expansion in correlation functions of all orders. A solution of the differential equation for a plane-parallel pore with asymmetric exponential wall potential is obtained.